STATE FISCAL POLICY IN MODERN ECONOMY AND THE EFFICIENCY OF ECONOMIC SYSTEMS - Alexander Vikulenko; Leonid Glukharev; Alexander Kolesnikov (Вестник Северо-Кавказского федерального университета)
The article describes the concept of the Central problem of economic science and economic practice - the effectiveness of production and distribution relations between the state and society in terms of oligopoly, not free market, competition, prices; efficiency NEP; multi-stage economy, monetary policy of the state; proportional taxation of income. It is necessary to stimulate the efficiency of economic activity of the country, provided that the effective formation and use of the state budget. The state is trying to use taxes to optimize consumption and make it reasonable. It is necessary to differentiate VAT rates depending on the dynamics of prices for comparable products and the dynamics of the physical volume of production. The achieved eficiency is evaluated twice: from the position of sellers and buyers. The eficiency of resources should be used in substantiating wage growth rates by comparing them with resource allocation, rather than with the productivity of living labour. Optimization ofprofits to the detriment of the wage Fund hinders the growth of the consumption Fund, refers to the future solution of the problem ofpoverty. Payment for labor contributes to the growth of savings and investment, socio - economic recovery of the country. The growth of Fund ofpayment for labour should be accompanied by a decrease of zarplatomer products. Fiscal policy of the state will be effective only in the democratization of economic life.